Pengolahan Limbah Cair Tempe menggunakan Sistem Bertahap ABR-MFCs dan Aerasi - Wijayanti, Sri Utami Bina; Nisa, Syadzadhiya Q. Z. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
Tempe industrial wastewater contains high organic matter, potentially polluting the environment if disposed of without adequate treatment. This study aims to analyze the effect of varying salt bridge types on the removal efficiency of Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and electrical energy production in a stepwise Anaerobic Baffled Reactor–Microbial Fuel Cells (ABR-MFCs) and aeration system. The study was conducted using a laboratory-scale ABR-MFCs reactor with tempe wastewater as the substrate. The salt bridge variations used were 1 M NaCl, 1 M KCl, and 1 M KNO₃. The treatment process was carried out for 120 hours in the ABR unit, followed by a 3-hour aeration process. The parameters tested included COD, TSS, pH, temperature, voltage, current, and electrical power density. The results showed that variations in salt bridges affected the efficiency of pollutant removal and electricity production. The KNO₃ salt bridge provided the best removal efficiency in the ABR unit with 96.38% COD removal and 72.73% TSS removal, as well as additional removal in the aeration unit of 40% for COD and 13.33% for TSS. Meanwhile, the KCl salt bridge produced the highest electrical performance with a voltage of 0.95 V, a current of 0.88 mA, and a power density of 167.2 mW/m². Based on the research results, the combination of the ABR-MFCs and aeration system has the potential to be an alternative technology for processing liquid waste in the tempeh industry that is effective and environmentally friendly while also being able to produce renewable electrical energy.